Cross-Cultural experience in UMP International Fiesta 2017 - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 19th Oktober – The organizing of International Fiesta 2017 from 27 to 29 October with the theme “Communitizing Internationalization” encourages the participation of local community as well as international community in UMP in various activities planned.